An algorithmic approach for the treatment of severe uncontrolled asthma. Issue 1 (6th March 2018) - Zervas, Eleftherios; Samitas, Konstantinos; Papaioannou, Andriana I.; Bakakos, Petros; Loukides, Stelios; Gaga, Mina
A small subgroup of patients with asthma suffers from severe disease that is either partially controlled or uncontrolled despite intensive, guideline-based treatment. These patients have significantly impaired quality of life and although they constitute <5% of all asthma patients, they are responsible for more than half of asthma-related healthcare costs. Here, we review a definition for severe asthma and present all therapeutic options currently available for these severe asthma patients. Moreover, we suggest a specific algorithmic treatment approach for the management of severe, difficult-to-treat asthma based on specific phenotype characteristics and biomarkers. The diagnosis and management of severe asthma requires specialised experience, time and effort to comprehend the needs and expectations of each individual patient and incorporate those as well as his/her specific phenotype characteristics into the management planning. Although some new treatment options are currently available for these patients, there is still a need for further research into severe asthma and yet more treatment options. Stepwise approach for the treatment of severe asthma http://ow.ly/rLPl30i0TyZ